Bacterial Pathogen Indicator Transport from Livestock Mortality Biopiles. Issue 5 (1st September 2015) - Michitsch, Robert; Jamieson, Rob; Gordon, Robert; Stratton, Glenn; Lake, Craig
Abstract : Biopiles can be used to dispose of slaughterhouse residuals (SLRs); however, the fate of pathogenic bacteria (e.g., pathogenic strains of Eschericia coli, Streptococcus fecalis ) in these systems is not well understood. The transport of these bacteria in water leaching from the biopile could represent a significant contamination source. This research examined the transport of Enterobacteriaceae and Enterococcaceae indicator bacteria from SLR biopiles. Three biopiles (2.6 m wide by 4.6 m long by 1.8 m high) were formed on soil layers in concrete cells that allowed for real‐time monitoring of environmental parameters, hydrologic flux, and indicator bacteria levels in effluent leaching from the piles. In biopile effluent, indicator bacteria populations decreased exponentially following biopile formation. Indicator bacteria loads in effluent constituted <0.01% of the initial indicator bacteria levels in the biopiles, which was attributed to retention, inactivation, and death. Nearly 90% of the total indicator bacteria loads coincided with large precipitation events (>15 mm d −1 ). Movement of the indicator bacteria through the biopiles and underlying soil appeared to be consistent with preferential flow phenomena. The populations of the Enterobacteriaceae indicators remained low in conditions of higher soil water content and lower biopile temperatures, whereas the Enterococcaceae indicator appeared to regrow in these conditions. This indicated that bacterial pathogen transport from a biopile could be a concern after the disappearance of conventional bacterial indicators, such as E. coli . Management considerations should attempt to divert excess water from entering a biopile, such as locating a biopile under a roof. Unsaturated biopile and soil conditions should be maintained to impede water flow through preferential pathways in the soil underneath a biopile. Core Ideas: Biopiles can dispose of slaughterhouse residuals that contain pathogenic bacteria. Indicator bacteria loads in effluent decreased due to retention, inactivation and death. Indicator bacteria movement through biopiles and soil was consistent with preferential flow. Enterococcaceae indicators regrew in higher soil water contents and lower biopile temperatures. Unsaturated biopile and soil conditions should be maintained to impede bacterial movement.